Stem Cell - The Future Little Master in Dentistry - Hasan, Md Nazmul; Darendeliler, Mehmet Ali (Update Dental College Journal, 2013)
Abstract not available DOI: http://dx.doi.org/10.3329/updcj.v2i2.15478 Update Dent. Coll. j: 2012; 2 (2): 01-02